Implementasi Algoritma Naïve Bayes Classifier Sinkronisasi Absensi Dengan Prestasi Akademik Pasraman Taman Dharma Widya - Hemdani Rahendra Herlianto; I Gede Krishna Yogananda Raken Putra (DPPM Universitas Pelita Bangsa, 2024)
Data mining is a technique that utilizes large amounts of data to obtain valuable information that was previously unknown and can be used to support important decision-making. In this study, the author attempts to mine customer data from an insurance company to determine whether the customers are categorized as current, less current, or delinquent in their payments. The existing data are analyzed using the Naive Bayes algorithm. Naive Bayes is one of the methods in probabilistic reasoning. The Naive Bayes algorithm aims to classify data into specific classes; the resulting patterns can then be used to predict students’ academic performance based on attendance records, enabling Pasraman Taman Dharma Widya to make appropriate decisions regarding the students.